2015
DOI: 10.1007/s00408-015-9796-5
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between the IL1B (−511 and +3954), IL1RN VNTR Polymorphisms and Tuberculosis Risk: A Meta-analysis

Abstract: Our results indicate there is a lack of association between the IL1B (-511 and +3954), IL1RN VNTR polymorphisms and TB risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…To show the importance of IL6 in TB, murine models with mycobacterial infections and models with a TB subunit vaccine indicated that IL6 was essential for the development of an optimal T-cell response [ 28 ]. IL6 mRNA and protein expression were significantly elevated in the serum of PTB patients [ 29 ]. MTB stimulates the secretion of IL6 which inhibits IFN-signaling, thus enabling MTB to evade eradication by a cellular immune response [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…To show the importance of IL6 in TB, murine models with mycobacterial infections and models with a TB subunit vaccine indicated that IL6 was essential for the development of an optimal T-cell response [ 28 ]. IL6 mRNA and protein expression were significantly elevated in the serum of PTB patients [ 29 ]. MTB stimulates the secretion of IL6 which inhibits IFN-signaling, thus enabling MTB to evade eradication by a cellular immune response [ 30 ].…”
Section: Discussionmentioning
confidence: 99%